Pelatihan Permainan Tradisional Bagi Guru Penjas Kota Jayapura - Ewendi W Mangolo; Ince Abdul Muhaemin M; Marsuki Marsuki; Andi Syaiful; Ansar CS (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The aim of this community service is to help students through elementary school physical education teachers to introduce traditional games and reduce children's habit of playing online games and help increase creativity by using materials available around them. This community service is carried out because of several problems such as (1) the lack of children who know traditional games so that their daily lives are filled with playing online games (2) social weaknesses that occur in the home environment, including playing on cellphones when spoken to, or being busy with gadget even though there is a friend beside him or he is sitting with family members. The implementation of this activity took place in the city of Jayapura. The stages of implementing this service activity are (1) problem identification (2) needs analysis; (3) designing coaching and mentoring; (4) carrying out mentoring; (5) monitoring and observing activity results; and (6) reporting and follow-up. The methods of community service are lectures, demonstrations and training. The results of this PKM which were carried out were seen from the questionnaires that were distributed, of the 20 participants who said they were good, 16 participants and 4 participants were very good.